STUDENT ENGAGEMENT WITH DRUG ABUSE AWARENESS EFFORTS: A CASE STUDY OF RIVERS STATE UNIVERSITY - Grace , Amadi Chidinma; Nwankwo , Ebuka James (International Research Journal of Arts and Communication, 2025)
The study aimed to ascertain the Rivers State University undergraduates’ awareness and response to below-the-line media campaigns on drug abuse. Specifically, the study sought to determine the level of exposure of Rivers State University students to below-the-line media campaign against drug abuse; find out if Rivers State University students adhere to below-the-line media campaigns on drug abuse among others. The research design adopted for this study was descriptive survey design. The population of this study consisted of the students of Rivers State University in Rivers State. The population of the institutions was obtained from the office of the Registrar of each of the institutions. The total population for the study was 24,325. In determining the sample size for this study, Taro Yamane mathematical formula was adopted. The sample size for the study was 400 and the study adopted the multi-stage sampling technique. Data for this study were obtained using copies of questionnaire. The research questions were analysed using the contingency tables were used to present data obtained from the questionnaire using weighted mean score. Findings from the study revealed that, all the respondents accepted to have heard, seen or read about drugs abuse in the campus. The result still revealed that the majority of the respondents had heard, seen or read about the drug to a low intensity among others. Based on the findings of this study, the researcher concludes that: media precipitates widespread awareness and as such served as a veritable medium for social mobilization. Below-the-line media such as billboard, signboard, posters, fliers, T-shirt, caps, handbills, etc demonstrated less competence in creating drug abuse exposure. The study, therefore, recommended that media, especially, on the below-the-line media should through their day-to-day reportage focus surveillance on the many ills and menace in the society so as to use them as themes for campaign. Also, campaigns should be designed such that they will have rudiments of the issues that form the subject matter of such campaigns. In this way, many people will see the need to key into the highlights of the message themes.